2019
DOI: 10.1021/acsomega.9b02551
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterion Nondetergent Sulfobetaine-Modified SnO2 as an Efficient Electron Transport Layer for Inverted Organic Solar Cells

Abstract: Tin oxide (SnO2) has been widely accepted as an effective electron transport layer (ETL) for optoelectronic devices because of its outstanding electro-optical properties such as its suitable band energy levels, high electron mobility, and high transparency. Here, we report a simple but effective interfacial engineering strategy to achieve highly efficient and stable inverted organic solar cells (iOSCs) via a low-temperature solution process and an SnO2 ETL modified by zwitterion nondetergent sulfobetaine 3-(4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Among the varieties of ETL materials, n-type low WF metal oxides, including ZnO, SnO 2 , and TiO 2 , etc., have been popularly used in OSCs and other organic electronics, such as perovskite solar cells and organic light-emitting diodes. [20][21][22][23][24][25][26] Although significant progress has been achieved based on metal oxide ETLs, the intrinsic drawbacks of such materials lead to unsatisfactory performances and stability, which need further improvements. Specifically, due to the ''Fermi level pinning effect,'' severe charge barriers exist at the interface between the metal oxide ETLs and organic semiconductors, resulting in inefficient charge transfer and accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the varieties of ETL materials, n-type low WF metal oxides, including ZnO, SnO 2 , and TiO 2 , etc., have been popularly used in OSCs and other organic electronics, such as perovskite solar cells and organic light-emitting diodes. [20][21][22][23][24][25][26] Although significant progress has been achieved based on metal oxide ETLs, the intrinsic drawbacks of such materials lead to unsatisfactory performances and stability, which need further improvements. Specifically, due to the ''Fermi level pinning effect,'' severe charge barriers exist at the interface between the metal oxide ETLs and organic semiconductors, resulting in inefficient charge transfer and accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…To further double-check the charge transport performances at the interface between the ETL and the active layer of the i-OSC device, the electrochemical impedance spectroscopy (EIS) was tested. [55][56][57][58] Typically, the clarification of the impedance spectra (IS) is straight linked with the engrafted bias voltage for the i-OSC devices. The photovoltaic cell will mainly conduct under recombination conditions when one manages IS assessments at the V OC , which could be searched in preceding reports.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Following this work, many research groups have reported solution-processed SnO 2 ETLs. [15,16] In particular, Alfa Aesar's aqueous SnO 2 colloidal solution, which was first adopted by Jiang et al, [17] is frequently used for this purpose. [18][19][20][21][22] Despite using the same colloidal solution, optimized deposition conditions reported in the literature, such as dilution conditions or film thicknesses, differ from lab to lab.…”
Section: Introductionmentioning
confidence: 99%